Revealing Knowledge Mining Intelligence: A Paradigm Shift from Data Mining in the Foreign Cooperation Context - Nuryanto, Adi; Wijaya, Chandra; Indriati Dwi Liestiawati, Fibria; Kuklin , Nikita (JPSI (Journal of Public Sector Innovations), 2024)
This article delves into the emerging concept of Knowledge Mining Intelligence (KMI) and its transformative impact within the realm of foreign cooperation. It examines the transition from conventional Data Mining practices to the advanced techniques inherent in KMI, offering a comprehensive framework for its implementation in the foreign cooperation information supply chain. The article explores the theoretical foundations of KMI, emphasizing its role as a catalyst for efficient foreign cooperation endeavors. Through a detailed analysis, it elucidates the profound shift from data-centric methodologies to knowledge-centric paradigms.